Inquiry-based reciprocal teaching module / Ting Pick Dew ... [et al.] - Ting, Pick Dew; Swanto, Suyansah; Pang, Vincent (2021)
Inquiry-Based Reciprocal Teaching (I-RT) Module was developed to provide Malaysian ESL educators with appropriate reading comprehension lessons to enhance the reading comprehension skills of Malaysian upper secondary ESL learners. With systematic guidance through embedded ADDIE instructional framework in Design and Development Research (DDR), and close reference to the Standard-Based English Language Curriculum for Secondary Schools (SBELC), this module weaved the four reciprocal teaching strategies: predicting, clarifying, questioning and summarizing, into the five cycles of inquiry-based reading: engagement, exploration, explanation, elaboration and evaluation. Designed to complement and ease the implementation of reading comprehension instruction, suggested reading lessons in this module were organized around classroom settings and can be applied to suit the differing needs of the learners. Adhering to the four language domains in SBELC namely personal, public, educational and occupational, this eight-unit module bases its reading activities on the four themes in SBELC: people and culture, health and environment, science and technology, and consumerism and financial awareness. The suggested lesson plans, teaching notes, worksheets and self-assessments allow the educators and learners to scaffold and construct meaning in a social setting through modelling, think-aloud and discussion, thus resulting in active learner engagement in the process of reading comprehension. With three recent publications and good content validity, this module serves as an authentic well-presented reading supplementary module which features well-thought strategies and activities to enhance learners’ reading comprehension.